The Differences between Pregnant Women with Obese and Non Obese towards Length of Labor Time in SADEWA Mother and Children Hospitasl, Yogyakarta - Supriyatiningsih, Husnawati (IISTE, 2015)
According to the study, the incidence of prolonged labor is 2.8%. The Prolonged labor can cause complications and can improve mortality both to the mother and the children.